Hazard Identiﬁcation of Laboratories Practice Incorporates with Particulate Matter (Pm) Concentration and Chemical Composition in University Laboratory Ambient - Mohd Alif Zamri (2018)
The identiﬁcation of particulate matter concentration and chemical composition concentration that incorporated with hazard identiﬁcation of laboratories practice in environmental lab and Bap 1.2 lab was performed from September, till October, 2017. PM; _5, PM4 and PM10 was determined by Low Volume Sampler (LVS), High Volume Sampler (HVS) and Microdust for time period of 6 hours per day. Besides that, hygrometer and wind speed were also used during the sampling period. The chemical compositions in the laboratory air were determined by extracting the quartz ﬁber ﬁlters and the concentration was measured using Atomic Absorption Spectrophotometer. Hazard identiﬁcation and risk assessment on the work activity in both laboratories was done during the sampling period by using HIRARC as a tool. The concentration of particulate matter and chemical composition in all samples did not exceed the limit set by American Society of Heating, Refrigeration, and Air Conditioning Engineers (ASHRAE) that was used as Malaysia standard. The average result of particulate matter and chemical composition for Bap 1.2 laboratory was higher than Environmental laboratory and risk at Bap 1.2 also higher that Environmental laboratory. This might be due to non- proper storage for chemical and waste.